Anti-Inflammatory Activities of Betulinic Acid: A Review - Oliveira-Costa, José Fernando; Meira, Cássio Santana; Neves, Maria Vitória Gomes das; Dos Reis, Bruna Padilha Zurita Claro; Soares, Milena Botelho Pereira (Frontiers in Pharmacology, 2022)
Inflammatory diseases have a high prevalence and has become of great interest due to the increase in life expectancy and the costs to the health care system worldwide. Chronic diseases require long-term treatment frequently using corticosteroids and non-steroidal anti-inflammatory drugs, which are associated with diverse side effects and risk of toxicity. Betulinic acid, a lupane-type pentacyclic triterpene, is a potential lead compound for the development of new anti-inflammatory treatments, and a large number of derivatives have been produced and tested. The potential of betulinic acid and its derivatives has been shown in a number of pre-clinical studies using different experimental models. Moreover, several molecular mechanisms of action have also been described. Here we reviewed the potential use of betulinic acid as a promissory lead compound with anti-inflammatory activity and the perspectives for its use in the treatment of inflammatory conditions.